A procedure for 3D simulation of seismic wave propagation considering source‐path‐site effects: Theory, verification and application - Wu, Mengtao; Ba, Zhenning; Liang, Jianwen (Earthquake engineering & structural dynamics, 2022)
This paper aims at obtaining a semi‐analytical and semi‐numerical 3D model of source‐to‐site seismic wave propagation due to kinematic finite‐fault sources. To this end, a two‐step procedure integrating the frequency‐wavenumber (FK) approach with the spectral element method (SEM) is proposed based on the concept of domain reduction. First, the broadband responses of a stratified crust are accurately calculated by using a novel FK approach and are converted into effective seismic inputs around the region of interest. After that, the seismic wavefields at local and regional scales arising from complex geological and topographical conditions are finely simulated using the SEM, and a perfectly matched layer absorbing boundary condition is simultaneously applied to realize the absorption of outgoing waves. In this procedure, a hybrid source modelling scheme that combines the low‐wavenumber deterministic and high‐wavenumber stochastic components on the fault plane is introduced, effectively addressing the high‐frequency motion radiated from the source rupture process. Subsequently, the proposed FK‐SEM procedure is verified step‐by‐step using the point source and finite‐fault source models. To illustrate the feasibility of the procedure, 3D physics‐based numerical simulations (PBSs) of two seismic events, including a historical Sanhe‐Pinggu earthquake and a well‐recorded Yangbi earthquake, are performed. The case studies validate that the proposed FK‐SEM procedure allows a significant reduction in computational effort and a substantial improvement in modelling resolution and can be applied to the source‐to‐site broadband synthetics of earthquake scenarios with limited resources. In addition, this coupled geophysics‐engineering simulation meets the requirements of time‐history analysis for engineering structures, which facilitates the study of soil‐structure interactions and regional‐scale building damage assessment.